Utilization of Zeolite Imidazolate Framework as an Adsorbent for the Removal of Dye from Aqueous Solution - Kang, Xiao-Zhen; Song, Zheng-Wei; Shi, Qi; Dong, Jin-Xiang (Asian Journal of Chemistry, 2013)
In this work, we have described the adsorption of dye acid blue 40 and methylene blue from aqueous solution onto isotypic zeolite imidazolate frameworks (ZIFs) such as ZIF-8 [Zn(mim)2] and ZIF-67 [Co(mim)2]. The results suggested that the charged sites at the external surface of zeolite imidazolate frameworks play a key role in dye adsorption. A similar adsorption capacity is observed for the uptake cationic dye methylene blue between ZIF-8 and ZIF-67, involving electrostatic interactions between the same N-extremities (belonging to mim linkers) and positively charged methylene blue. For anionic dye acid blue 40, the adsorption capacity for ZIF-67 is nearly three times higher than that of ZIF-8, involving electrostatic interactions between low-coordinated metal cations of zeolite imidazolate frameworks and negatively charged groups of acid blue 40 and Co cations in ZIF-67 have higher affinity with the SO3– groups of acid blue 40.